Review on fate and mechanism of removal of pharmaceutical pollutants from wastewater using biological approach - Tiwari, Bhagyashree; Sellamuthu, Balasubramanian; Ouarda, Yassine; Drogui, Patrick; Tyagi, Rajeshwar D.; Buelna, Gerardo (Bioresource technology, 2017)
[Display omitted] •Pharmaceutical residues in aquatic environment causes ecotoxicity.•CAS process is not efficient in removal of pharmaceuticals residues.•MBR process would be a promising techniques in removal of these micro-pollutant.•Metagenomics study of HWWTP will help in development of optimized MBR process. Due to research advancement and discoveries in the field of medical science, maintains and provides better human health and safer life, which lead to high demand for production of pharmaceutical compounds with a concomitant increase in population. These pharmaceutical (biologically active) compounds were not fully metabolized by the body and excreted out in wastewater. This micro-pollutant remains unchanged during wastewater treatment plant operation and enters into the receiving environment via the discharge of treated water. Persistence of pharmaceutical compounds in both surface and ground waters becomes a major concern due to their potential eco-toxicity. Pharmaceuticals (emerging micro-pollutants) deteriorate the water quality and impart a toxic effect on living organisms. Therefore, from last two decades, plenty of studies were conducted on the occurrence, impact, and removal of pharmaceutical residues from the environment. This review provides an overview on the fate and removal of pharmaceutical compounds via biological treatment process.